Chloroplast DNA variation of Shorea acuminata Dyer in Eastern Sumatra assessed by microsatellite markers - ZULFAHMI ZULFAHMI; ISKANDAR ZULKARNAEN SIREGAR; ULFAH JUNIARTI SIREGAR (Biodiversitas Journal of Biological Diversity, 2010)
Zulfahmi, Siregar IZ, Siregar UJ (2010) Chloroplast DNA variation of Shorea acuminata Dyer in Sumatra assessed by microsatellite markers. Biodiversitas 11: 107-111. Shorea acuminata Dyer is member of the Dipterocarpaceae family. It is ecologically and commercially important in the Indonesian region. In the present study, chloroplast microsatellites (cpSSRs) were used to study the distribution of chloroplast DNA haplotypes and to assess the variation within and among populations of S. acuminata from Riau and Jambi provinces eastern part of Sumatra. Based on chloroplast microsatellite analysis, six haplotypes were observed for S. acuminata,namely haplotype P, Q, R, S, T, and U, respectively. The high haplotype variation was detected in Bukit Barisan National Park (TNBT) population (five haplotypes); it may be due to TNBT population status as national parks (conservation area) under government protection. The value of genetic differentiation measured for S. acuminata was Gst = 0.150. The Gst values in this study is lower than the mean Gst value estimated in angiosperms plant for maternally inherited. Information on the status of genetic variation of the species in this study could be used as scientific consideration in formulating appropriate strategies for conservation and sustainable utilization ofgenetic resources.Key words: Dipterocarpaceae, Shorea acuminata, chloroplast microsatellites, genetic variation